ANALISIS ESTETIKA PUISI DALAM PLATFORM INSTAGRAM: KAJIAN STILISTIKA PADA PUISI “BEBERAPA SAAT” KARYA NATASHA RIZKY - Jubaedah, Siti; Sulistiawan, Dellana Ismi; Yunus, Syarifudin (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This study aims to analyze the aesthetics of a poem entitled "Semua Saat" published through the Instagram platform, using a stylistic approach. This study focuses on linguistic elements such as diction, style, repetition, and aesthetic nuances. The results of the analysis show that even though it was published on social media, the poem has a depth of meaning, emotional strength, and a strong stylistic structure, so that it can still be studied as a quality literary work. The poem "Semua Saat" proves that literary works published through Instagram still have high aesthetic value if written with the right choice of language. Through a stylistic approach, this poem shows a richness of expression in the diction, repetition, and figures of speech used. The inner journey in this poem, from apparent calm to spiritual sincerity, creates a deep and touching aesthetic value. Social media does not reduce the quality of a poem, but rather opens up new space for poets to reach a wider readership. With proper analysis, works like this can still be studied scientifically and appreciated as part of the development of contemporary literature.